The current challenge to restore factual truth in the age of disinformation and post-truth: the case of the fact-checker ‘Polígrafo’ in Portugal - Rodrigues, Luís Pedro Ribeiro (2023)
Fact-checking emerges as a new journalistic approach in the scope of measures to combat disinformation. It verifies the veracity of information circulating in the media ecosystem, especially on the Internet and online social media. However, fact-checking has some limitations. For example, the human ability to check information is not sufficient for the massive production of false information. Moreover, journalism is complex and often deals with partially true or partially false information. These issues are addressed in the first part of the paper, situating fact-checking in the social context of disinformation and post-truth. Then, the product developed by the fact-checker “Polígrafo” in Portugal is described and interpreted. The analysis based on theoretical and empirical data can help improving this new journalistic approach without disregarding its contribution to combating disinformation. The results confirm social media as the preferred media for selecting information to be analysed and the option for a fact-checking model with a verdict based on a rating scale of veracity. Furthermore, it was observed an effort to contextualise the fact. It also includes interviews with people involved in the event, rhetorical questions giving a didactic tone to the text, bold marking of the most relevant information, and hyperlinks to other information sources.